Effect of hydrophobic montmorillonite (MMT) on PVDF and PEI hollow fiber membranes in gas–liquid contacting process: a comparative study. Issue 126 (8th December 2015) - Rezaei-DashtArzhandi, M.; Ismail, A. F.; Bakeri, Gh.; Hashemifard, S. A.; Matsuura, T.
Abstract : Porous polyvinylidene fluoride (PVDF) and polyetherimide (PEI) hollow fiber mixed matrix membranes are successfully fabricated for CO2 absorption via membrane contactor. Abstract : Porous polyvinylidenefluoride (PVDF) and polyetherimide (PEI) hollow fiber mixed matrix membranes (MMMs) were spun under the same spinning conditions for CO2 absorption experiment via membrane contactor. The effects of montmorillonite (MMT) loading on thermodynamic and kinetic aspects of phase inversion as well as the membrane properties were investigated using various analytical characterization methods. MMT embedment into PVDF lowered the thermodynamic stability while making the solvent/nonsolvent exchange in the phase inversion faster, which resulted in the formation of thinner skin layer, thicker finger-like layer and thinner sponge-like layer. As a result, the N2 gas permeance increased considerably. As for the PEI, the high hydrophobicity of the incorporated clay particles slowed down the rate of solvent/nonsolvent exchange and subsequently thicker skin layer as well as more compact sublayer structure with narrower finger-like pores was formed. Hence, a considerable reduction in the rate of gas permeation for the PEI MMMs was observed. In addition, both PVDF and PEI membranes experienced significant increase in the contact angle and LEPw by the presence of hydrophobic MMT in the system. Physical CO2 absorption with distilled water was performed using the hollow fiber gas–liquid membrane contactor. The absorption flux was enhanced by the MMT embedment for both PVDF and PEI but the flux enhancement of PEI was more pronounced than the PVDF. However, the long-term absorption stability test over 15 days revealed that the flux of the MMT incorporated PEI hollow fiber deteriorates considerably with time due to the intrinsically high hydrophilicity of PEI material.